Estudo sobre estabilização de solo com material fresado de pavimentação asfáltica - Araújo Junior, Luiz Paulo Vieira de (2019)
In Brazil, the most commonly used means of transport for people and the locomotion of loads is the road, and the paved roads show that most of them have asphaltic coating, as well as urban roads. However, to maintain these roads under acceptable traffic and safety conditions, regular maintenance or restoration interventions are required. Among these processes for the rehabilitation of the asphalt coating, there is the milling process of the asphalt layer, which consequently generates a large amount of waste that needs a final destination. In this case, the reuse of the milled material is an important topic to be studied, since, besides containing properties that can provide an increase of resistance in the layers of pavement, can reduce the execution costs generating less impacts to the environment, since the material to be discarded will be reused. In addition, it is not necessary to extract the materials from the deposits, as well as the need for no deposit areas. From this scenario, we can highlight that the importance of the present study was to seek an alternative to the reuse of waste. In this sense, we had as objective to evaluate the behavior and performance of the mixtures of lateritic and nonlateritic tropical soils with milled asphalt material for possible use in base layers, sub-base and reinforcement of subgrade of flexible pavements for urban roads. The experimental methodology was carried out according to the following steps: selection and collection of five soils of the region of São Carlos-SP; identification of soils, namely: soils 1, 2, 3, 4 and 5; conducting soil characterization tests; and, finally, classification according to the MCT and HRB methodology. Thus, the asphalt milled material was collected and the characterization of the residue was carried out, being the same used in the mixture without any treatment process. The experimental part by means of simultaneous Support California Index (ISC) tests in the Normal and Intermediate compaction energy, in which a variation of percentages of milled material was applied in relation to the pure soils used. The percentages were increased in predefined proportions of 10% in 10% of the recycled material (milling) in substitution to the soil until reaching 50%. The variation of the ISC and the expansion in different moisture contents for the soils purely as for the different mixtures were evaluated. Therefore, based on the results of the tests carried out on the soils analyzed, it was verified that the use of milled material in layers of subgrade reinforcement, sub-base and base of low traffic pavements or urban pavements, can be an alternative technically feasible, provided that the conditions for application are met.